1987
DOI: 10.1111/j.1600-0447.1987.tb02759.x
|View full text |Cite
|
Sign up to set email alerts
|

Zuclopenthixol acetate in Viscoleo® ‐ a new drug formulation

Abstract: Eighty-three acutely disturbed, psychotic patients were included in an open multicentre study. The aim of the study was to evaluate the clinical effect of zuclopenthixol acetate in Viscoleo (CPT-A). Each patient received from one to four intramuscular injections of CPT-A during the 6-day study period. The duration of action after one injection was between 2 and 3 days and doses from 50 mg to 150 mg were sufficient for most patients. Treatment with CPT-A caused a pronounced and rapid reduction of the psychotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Several studies show the efficacy of zuclopenthixol for the treatment of acute psychosis or exacerbated chronic psychosis (Gravem and Bugge, 1981;Sechter et al, 1981;Lang and Winteler, 1983;Mann et al, 1985;Bourdouxheet al, 1987), but little information is yet available about zuclopenthixol acetate (Amdisen et al, 1987;Kuefferle et al, 1987). Our results confirm that this prodrug is a useful antipsychotic medication for the treatment of acute psychotic episodes or acute deteriorations of a chronic psychotic state (Amdisen et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show the efficacy of zuclopenthixol for the treatment of acute psychosis or exacerbated chronic psychosis (Gravem and Bugge, 1981;Sechter et al, 1981;Lang and Winteler, 1983;Mann et al, 1985;Bourdouxheet al, 1987), but little information is yet available about zuclopenthixol acetate (Amdisen et al, 1987;Kuefferle et al, 1987). Our results confirm that this prodrug is a useful antipsychotic medication for the treatment of acute psychotic episodes or acute deteriorations of a chronic psychotic state (Amdisen et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Injectable neuroleptics were developed for the management of acute psychoses in people who refused to take oral neuroleptics in the initial stages of their treatment (Amdisen et al, 1987). These drugs are used to alleviate anxiety, have various durations of action depending on formulation, and have few side effects when used appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary to the recommendations from the manufacturer, and to the guidelines given in prescribing manuals, which suggest a course of injections is usually optimal. [8], [9], [10] Just under half ( n = 40) of the respondents routinely gave ZA with another psychoactive medication, most frequently a benzodiazepine (clonazepam being most frequently used). Sedation was cited as being the most frequent side effect of ZA, and although EPSE were recognised as a complication of treatment, respondents rated this as relatively uncommon (on a linear scale of 1-5, mean score was <3).…”
Section: Establishing a Need For Specific Guidelines For Use Of Zamentioning
confidence: 99%
“…In sum, there was a reasonable consistency between trials on the following: Several studies suggested that, depending on the individual's diagnosis, a differential response to ZA can be expected. That is, those with an exacerbation of chronic psychotic illness or acute mania tended to show a more rapid response, evidenced by decline in clinical global impression (CGI) score ( P < 0.0001) 8 and Bech Rafaelsen Mania scale (BRMAS) scores ( P < 0.001). [8], [14] There was reasonable agreement that the time of onset of sedation was between 15-90 minutes and that this level of sedation increases to reach a maximum after 8 hours.…”
Section: What Does the Literature Say?mentioning
confidence: 99%
See 1 more Smart Citation